R/V NATSUSHIMA NT06-08 Cruise Data - JAMSTEC (JAMSTEC, 2006)
[CRUISE DATA] This site includes a cruise dataset acquired in NT06-08 on R/V NATSUSHIMA from 2006-04-28 to 2006-05-14.
Observation contents: Bathymetry, Expendable Bathythermograph, Rock Sample
Keywords: Research cruise; R/V NATSUSHIMA; oceans